A glucose sensor via stable immobilization of the GOx enzyme on an organic transistor using a polymer brush. Issue 2 (25th September 2014) - Welch, M. Elizabeth; Doublet, Thomas; Bernard, Christophe; Malliaras, George G.; Ober, Christopher K.
ABSTRACT Recently, there has been significant research in the area of organic electrochemical transistors (OECTs) because of their superior aptitude of chemical and biological sensing. Here it is shown for the first time the incorporation of polymer brushes to a transistor. Polymer brushes were chosen for their biocompatible properties and their ability to covalently tether enzymes and other biomolecules to different surfaces. OECTs were fabricated from the conducting polymer poly(3, 4‐ethylenedioxythiophene) doped with poly(styrene sulfonate), PEDOT:PSS, and polymerized from the surface a mixed polymer brush of poly(glycidyl methacrylate) and poly(2‐hydroxyethyl methacrylate). The brushes were functionalized with glucose oxidase and measured in terms of electrical performance and long‐term stability. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 372–377